Pengaruh Jumlah Sudu Pengaduk Terhadap Pola Pencampuran dan Konsumsi Daya Listrik pada Mixer Vertikal - Hindro Prasetyo, Bayu; Rubiono, Gatut; Suryadhianto, Untung (Prodi Teknik Mesin Universitas PGRI Banyuwangi, 2020)
The effective mixing can be seen from the length of the stretching, the number of folding and the consumption of electric power required in the process. A suitable type of stirrer, a varying number of blades, can enrich the flow pattern created. This study aims to determine the effect of the number of mixing blades on the mixing pattern and the consumption of electric power in the vertical mixer. the number of blades varied (number of blades 4,6,8 pieces). The test material is given a dye, so that we can see the mixing pattern that occurs for electrical power consumption can be calculated with a digital multimeter. From the results of this study, we will be able to measure the length of the stretching and the number of folding produced in rounds 1-4. And will be compared with the required electric power consumption. The results showed that the more mixing blades used, the less power consumption required. The more blades used, the longer the stretching results. The more mixing blades used, the more folding can be produced..Keywords: mixing, stretching, folding, number of blades